Antibiotic Prophylaxis in Prostate Biopsies: Contemporary Practice Patterns in Germany - Boehm, Katharina; Siegel, Fabian P.; Schneidewind, Laila; Kranz, Jennifer; Spachmann, Philipp; Frank, Tanja; Huck, Nina; Imkamp, Florian; Pelzer, Alexandre (Frontiers in Surgery, 2018)
Purpose Prostate biopsy (pbx) is the most common outpatient procedure in urology. Complications are urinary tract infections, including hospitalisation and sepsis. Recommendations on antibiotic prophylaxis (apx) are scarce and healthcare data are not available. The study addressed the following endpoints: the duration and spectrum of antimicrobial prophylaxis in transrectal and transperineal prostate biopsy in the hospital and the practice setting. Methods A questionnaire compiled data about age, gender, board certification and place of work. Information about the frequency of pbx, duration and type of apx, usage of disinfecting lubricant and urine or rectal swab cultures was collected. The study refers to German urologists. Results Overall 478 urologists answered the questionnaire. 15.5% (74) of respondents were residents. 50.8% (243) of urologists work in a practice; the rest in a hospital. Only 4.8% do not perform pbx. Transrectal pbx are performed a median of 2 times a week. The majority (446, 98%) prescribe an apx, mostly fluoroquinolones (407, 89.5%). In total, 10.1% (46) of the participants use a single-shot-antibiotic prophylaxis. Apx has a median duration of 4 days. One third use a disinfecting lubricant. Urine and rectal swab cultures are analysed by 45.5% (207) and 24.4% (111) respectively. Conclusion Most urologists prescribe an extended apx for both transrectal and transperineal pbx. Perineal pbx is still a deviation from everyday practice and not an established alternative to transrectal pbx. Urologists are aware of the increasing fluoroquinolone-resistance and are adapting with rectal swab- and urine cultures. Further studies need to evaluate alternatives to 5-day apx and results should be addressed in our guidelines. This is of importance in light of the increasing resistance rates and fluoroquinolone side effects.